Development of a Rapid and Sensitive Probe for Colorimetric Detection of Ni2+ Ion in Water Sample by β-Cyclodextrin Stabilized Silver Nanoparticles - Ahmad Fathoni; Muhammad Eka Prastya; Zetryana Puteri Tachrim; Abdul Aji; Agustina Sus Andreani; Farrah Nurkhaliza (Indonesian Journal of Chemistry, 2023)
A rapid and selective colorimetric detection of Ni2+ was developed using silver nanoparticles (AgNPs) with β-cyclodextrin (β-CDs) as reducing and stabilizing agents. Characterization was assessed by spectrophotometer UV-vis, Fourier transform infra-red (FTIR), transmission electron microscopy (TEM), and particle size analyzer (PSA). The AgNPs-β-CDs were relatively stable after being stored for 5 months. The addition of Ni2+ to the AgNPs-β-CDs shifted the surface plasmon resonance (SPR) band at 409 nm. Synthesized AgNPs-β-CDs had a spherical shape and an average size of 25.07 ± 0.66 nm (analyzed by TEM) and 33.63 ± 0.25 nm, as confirmed by PSA. AgNPs-β-CDs as colorimetric sensors for Ni2+ ions had a good linear calibration curve at 409 nm with the R2 value of 0.9993. The limit of detection (LoD) was found to be 33.30 ppb, while the limit of quantification (LoQ) was 111.0 ppb. This sensor had been applied to a seawater sample from Ancol Beach, North Jakarta, Indonesia and it exhibited good precision and accuracy. In this work, β-CDs-synthesized AgNPs were able to detect Ni2+ ions and were beneficial as an alternative method for Ni2+ screening in environmental samples.